Complex characteristics of landscape components affected by the disaster at the Kahovka Hydropower Plant - Dovhanenko, D. О.; Довганенко, Д. О.; Yakovenko, V. M.; Яковенко, Володимир Миколайович; Brygadyrenko, V. V.; Бригадиренко, В. В.; Boyko, Olexandra O.; Boyko, O. O.; Boyko, A. A.; Boyko, O.; Boyko, A.; Бойко, Олександра Олександрівна (Oles Honchar Dnipropetrovsk National University, 2024)
The paper provides an in-detail analysis of the flooding in Kherson and Mykolaiv oblasts as a result of the explosion at the Kahovka Hydropower Plant (HPP). We considered the possibility of using a combined analysis of the data of on-ground and remote monitoring of the course and consequences of the flooding. Based on the materials of the Ukrainian Hydometeorological Center of the State Service of Ukraine, we determined control points of chronology of the events and the dynamics of the main hydrometric indicators. The flooding began on 05/06/2023, the water returning back to the regular levels on average on 26/06/2023. The highest levels of water were observed in the period between June 7 and June 9, 2023. The synchronicity of the satellite surveillance of the territory during this time is representative. Based on the parameters of spatio-temporal resolution and degree of cloud cover, we chose the satellite images from Landsat 9 as the basic materials for our study. Using a modified normalized water index, we identified changes in the water area in the indicated time period. Using a digital model of the territory’s relief, we elaborated the zone of spread of the water surface in areas with dense vegetative cover. We found flooded zones where the water was much higher than the maximal levels recorded at the hydrological-monitoring checkpoints. The elucidation of estimations of the flooding zone revealed the components of natural landscapes that have been affected by the techogenic catastrophe. The flooding pummeled the azonal landscape complexes and complexes of above-floodplain terraces and coastal plains. The results of our study are an important step towards assessing the degradation of the downstream-Dnipro ecosystem. They will lay the groundwork for designing plans to liquidate the aftermath of the emergency and adaptation measures in the conditions of increasing risk of devastating technogenic events. У роботі детально проаналізовано підтоплення Херсонської та Миколаївської областей внаслідок вибуху на Каховській ГЕС. Розглянуто можливість використання комбінованого аналізу даних наземного та дистанційного моніторингу перебігу та наслідків затоплення. За матеріалами Українського гідрометцентру Держслужби України визначено контрольні точки хронології подій та динаміку основних гідрометричних показників. Паводок розпочався 06.05.2023, вода поверталася до нормального рівня в середньому 26.06.2023. Найвищі рівні води спостерігалися в період з 7 по 9 червня 2023 року. Синхронність супутникового спостереження території за цей час є репрезентативною. Виходячи з параметрів просторово-часової роздільної здатності та ступеня хмарності, ми обрали супутникові знімки Landsat 9 як базові матеріали для нашого дослідження. За допомогою модифікованого нормалізованого індексу води виявлено зміни в акваторії за вказаний період часу. За допомогою цифрової моделі рельєфу території визначено зону поширення водної поверхні на ділянках з густим рослинним покривом. Ми виявили зони підтоплення, де рівень води значно перевищував максимальні рівні, зафіксовані на пунктах гідрологічного моніторингу. З’ясування оцінок зони затоплення дозволило виявити компоненти природних ландшафтів, які постраждали від техногенної катастрофи. Паводок завдав шкоди азональним ландшафтним комплексам і комплексам надзаплавних терас і прибережних рівнин. Результати нашого дослідження є важливим кроком до оцінки деградації екосистеми нижньої течії Дніпра. Вони закладуть основу для розробки планів ліквідації наслідків НС та адаптаційних заходів в умовах підвищення ризику руйнівних техногенних явищ.
Комплексна характеристика компонентів ландшафту, що постраждали від катастрофи на Каховській ГЕС
Бойко Олександра Олександрівна https://orcid.org/0000-0002-7299-9920
Keywords: flood surge; паводковий нагін; flooding; затоплення; remote monitoring; віддалений моніторинг; normalized water index; нормований індекс води; landscape complexes; ландшафтні комплекси; Ukraine; Україна